Improving Students’ Level of Confidence in Oral Presentation via Video Recording Task - Nurizah Md. Ngadiran; Hazila Kadir @ Shahar; Meizareena Mizad (Development in Language Studies, 2024)
Anxiety has significantly impacted students’ speaking performance in classrooms. Implementing a video recording task as a teaching and learning option, not only reduces anxiety, but would also positively influence students’ speaking abilities. Therefore, this research aimed to explore how employing a video recording task could alleviate students’ anxiety in oral presentation. The informants were Universiti Tun Hussein Onn Malaysia (UTHM) Kor SUKSIS trainees attending UTHM Kor SUKSIS Public Speaking Course 2023. The research implemented a descriptive qualitative approach, and the data were gathered through interview sessions. Interview sessions revealed that students felt notably more confident during task presentations. In conclusion, incorporating video recording tasks could effectively mitigate students’ anxiety in oral presentation performances.